Hubungan Tingkat Pengetahuan dengan Perilaku Hidup Bersih dan Sehat pada Siswa Sekolah Dasar: The Relationship Between Knowledge Level and Clean and Healthy Living Behavior Among Elementary School Students - Putra, Mega Revangga (Chakra Brahmanda Lentera Institute, 2026)
Clean and Healthy Living Behavior (PHBS) is an essential component in maintaining and improving health status, particularly among elementary school students. The implementation of PHBS from an early age in the school environment is expected to foster sustainable healthy lifestyle habits. One of the factors presumed to influence the practice of PHBS is the level of students’ knowledge. This study aimed to determine the relationship between the level of knowledge of clean and healthy living behavior and clean and healthy living behavior among sixth-grade students of SDN 8 Ngronggo, Kediri City. This study employed a quantitative research design using an analytical survey method. The instruments used consisted of an eight-item PHBS knowledge test and an eight-item clean and healthy living behavior questionnaire, with data analysis conducted using the Product Moment correlation test. The research subjects totaled 71 students. The results showed that 99.3% of students had a high level of PHBS knowledge, and 94.6% of students had implemented clean and healthy living behavior. The correlation analysis produced a coefficient value of 0.245, indicating that the relationship between PHBS knowledge and clean and healthy living behavior was categorized as weak. There is a weak relationship between the level of knowledge of clean and healthy living behavior and the implementation of such behavior among students.